2015
DOI: 10.26848/rbgf.v8.0.p471-483
|View full text |Cite
|
Sign up to set email alerts
|

Emergência e Crescimento Inicial de Plântulas de Cebola Sob o Aumento da Temperatura e Concentração de CO2 (Onion Seedlings Emergence and Initial Growth Under Increased Temperature and CO2)

Abstract: As mudanças climáticas, especialmente o aumento da temperatura e da concentração de gases de efeito estufa na atmosfera , afetarão o crescimento e desenvolvimento das plantas. O objetivo deste trabalho foi avaliar o efeito de aumento da temperatura e da concentração de CO2 na emergência de plântulas de cebola das cultivares Alfa São Francisco, Franciscana IPA 10, Vale Ouro IPA 11 e Serena .O experimento foi conduzido em câmaras de crescimento, com controle de umidade, luminosidade, temperatura e CO2, durante 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The leaf number variable indicates that this accession is more adapted to air temperatures ranging between 20 and 30 o C. It was also observed that the lowest tested temperature (10 o C) provided the least number of leaves, differing significantly from the other treatments. In the photosynthetic process, CO 2 fixation and reduction occurs slowly at low temperatures, increasing with heating, until reaching the optimum temperature (Costa et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The leaf number variable indicates that this accession is more adapted to air temperatures ranging between 20 and 30 o C. It was also observed that the lowest tested temperature (10 o C) provided the least number of leaves, differing significantly from the other treatments. In the photosynthetic process, CO 2 fixation and reduction occurs slowly at low temperatures, increasing with heating, until reaching the optimum temperature (Costa et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…At temperatures above the optimum one, the carboxylation of ribulose 1,5-bisphosphate (RuBP) decreases considerably, due to the temperature increase, and the O:CO 2 ratio is modified; the solubility of CO 2 decreases in relation to that of O 2 and, thus, photorespiration is favored, reducing the photosynthetic yield. There is also an unbalance promotion in the input and output of CO 2 by plants (Costa et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations